Preoperative transaortic forward flow: Prediction of surgical outcomes in patients with DCM and mitral regurgitation. (September 2015) - Hirota, Masanori; Yoshida, Minoru; Hoshino, Joji; Kondo, Taichi; Isomura, Tadashi
Background: In patients with dilated cardiomyopathy and mitral regurgitation, preoperative prognostic factors are very important. Methods: We hypothesized that preoperative transaortic forward flow might be related to postoperative survival, despite mitral regurgitant volume. We retrospectively evaluated surgical outcomes and echocardiographic parameters, including forward flow through the aortic valve. Results: Seventy-nine patients (54 males, 25 females; mean age 59 ± 12 years) with dilated cardiomyopathy and mitral regurgitation were divided into two groups according to postoperative outcome: 19 patients in group A suffered cardiac death, 60 in group B survived or died of another cause. In group A, death occurred after 227 ± 116 days, group B patients survived (except one who died of infection) for 505 ± 446 days; p  < 0.01. Preoperatively, there was no significant difference in ejection fraction, end-diastolic and end-systolic volume index, mitral regurgitant volume, effective regurgitant orifice area, or right ventricular systolic pressure. Preoperative transaortic forward flow was significantly lower in group A vs. group B (1.57 ± 0.33 vs. 1.81 ± 0.46 L m −2 ; p 0.04). In group B, transaortic forward flow was increased significantly before discharge (1.81 ± 0.51 vs. 2.43 ± 0.62 L m −2 ; p  < 0.01). Ejection fraction was significantly alleviated before discharge (28% ± 9% vs. 23% ± 8%; p  < 0.01) and recovered to the preoperative value without repeat dilation of the left ventricle in late follow-up. Conclusions: Preoperative transaortic forward flow may be a predictor of survival in patients with dilated cardiomyopathy and mitral regurgitation, irrespective of mitral regurgitant volume.